Nontuberculous Mycobacteria in Humans, Animals, and Water in Zambia: A Systematic Review - Zulu, Mildred; Monde, Ngula; Nkhoma, Panji; Malama, Sydney; Munyeme, Musso (Frontiers in Tropical Diseases, 2021)
Nontuberculous mycobacteria (NTM) are environmental opportunistic pathogens of humans and animals that are emerging with a serious public health impact particularly in individuals with Acquired Immunodeficiency Syndromes. Recent scientific evidence is shifting from NTMs being known as traditional environmental organisms to serious pathogenic organisms in both animals and humans. In humans, factors attributable to this rise have been linked mainly to Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome pandemic without in-depth information that can explain the observed rise in animal populations. This study was therefore formulated to review available information on the prevalence of NTM in humans, animals and the environment, its species distribution, zoonotic potential and public health importance in Zambia. This review was conducted in accordance with PRISMA guidelines. A literature search was done in PubMed and Google scholar using predefined search terms such as ‘nontuberculous mycobacteria’, ‘atypical mycobacteria’, ‘mycobacteria other than mycobacterium tuberculosis’ and ‘Zambia’, in combination with Boolean operators (AND, OR). This particular systematic review draws findings based on literature search between 2000 and 2020. Through literature search 243 papers were identified, 23 duplicates were identified and removed and 205 articles were excluded as they did not meet the inclusion criteria. The full text of the remaining 15 articles were considered for this review. The overall prevalence of NTM in humans was 24.39%, in water 21.5%, cattle 17.9% and Kafue Lechwe 7.1%. Mycobacterium intracellure was the most common isolated nontuberculous mycobacteria in humans and cattle while Mycobacterium gordonae was the most common in water, and Mycobacterium stomatepiae sp Nov in Kafue Lechwe. Nontuberculous mycobacteria are an emerging public health threat in Zambia and Mycobacterium intracellure is the most commonly isolated nontuberculous Mycobacterium in humans and cattle, Mycobacterium gordonae in water, and Mycobacterium stomatepiae sp nov in Kafue Lechwe. There is need for molecular information on the zoonotic transmission of nontuberculous mycobacteria in Zambia. Increased awareness of nontuberculous mycobacteria diseases among clinicians and laboratory personnel is crucial for patient management and an essential step for facilitating the identification of nontuberculous mycobacteria species in laboratories